Mercapto-benzothiazolyl based ruthenium(ii) borate complexes: synthesis and reactivity towards various phosphines. Issue 21 (17th April 2019) - Zafar, Mohammad; Rongala, Ramalakshmi; Pradhan, Alaka Nanda; Pathak, Kriti; Roisnel, Thierry; Halet, Jean-François; Ghosh, Sundargopal
Abstract : Ruthenium complexes featuring phosphinate and dual Ru⋯H–B interactions between Ru and B–H bonds of borate ligands supported by mercapto-benzothiazolyl heterocycles have been synthesized. Abstract : The synthesis and reactivity of ruthenium complexes containing an anionic boron based ligand, supported by mercapto-benzothiazolyl heterocycles are presented. Specifically, the reaction of [(η 6 - p -cymene)RuP(OMe)2 ORCl2 ], (1a : R = Me;1b : R = H) with [H2 B(mbz)2 ] − (mbz = 2-mercaptobenzothiazolyl) at room temperature afforded a series of borate complexes, namely [(L)Ruκ 3 -H, S, S′-H2 B(L)2 P(O)(OMe)(HL)], 2, [Ruκ 3 -H, S, S′-H2 B(L)2 2 ], 3 and [(κ 2 - N, S -L)P(OMe)3 Ruκ 3 -H, S, S′-H2 B(L)2 ], 4a ; (L = C7 H4 NS2 ). The pivotal feature of2 is the coordination of the Ru centre with a phosphorus atom of secondary phosphine oxide and mercapto-benzothiazolyl ligands. On the other hand, 3 features dual Ru⋯H–B interactions between Ru and B–H bonds of [H2 B(mbz)2 ] − . Interestingly, along with3, compound [(κ 2 - N, S -L)P(OPh)3 Ruκ 3 -H, S, S′-H2 B(L)2 ], 4b (L = C7 H4 NS2 ), was isolated upon treatment of the same borate with [(η 6 - p -cymene)RuCl2 P(OPh)3 ], 1c, which is stabilized by δ-B–H interactions and one phosphite ligand. Furthermore, compound3 promptly reacts with P(OR)3 to generate [(OR)3 PRu-κ 2 -S, S′-H2 B(L)2 κ 3 -H, S, S′-H2 B(L)2 ], (5a : R = Me, 5b : R = Ph; L = C7 H4 NS2 ) by breaking one of the Ru⋯H–B interactions. Upon heating, compound5a converts into [(OMe)2 OPRuκ 2 -S, S′-HB(L)2 κ 3 -H, S, S′-H2 B(L)2 ], 6a (L = C7 H4 NS2 ) by release of methane gas. Compound6a is a unique example wherein the boron atom of the borate ligand is bound to an oxygen atom of the phosphite unit. In contrast, the thermolysis of3 with PR2 R′ yielded [Ruκ 3 -H, S, S′-H2 B(L2 )(PR2 R′)2 (L)], (7a : R = Me, R′ = Ph;7b : R = Ph; R′ = Me; L = C7 H4 NS2 ), respectively, revealing the incorporation of two triphosphine ligands in the coordination sphere of ruthenium. Density functional theory (DFT) calculations were undertaken to provide an insight into the electronic structures of the complexes.